Iranian identity, American experience philosophical reflections on race, rights, capabilities, and oppression - Alavi, Roksana, 1973- (Philosophy of race., 2021)
"This multidisciplinary book brings the topics of rights, identity, and race together to examine what it means to be oppressed, how oppression works, and what we both as individuals and as a community can do about it, using the Iranian American community as a case study"--